Journal: Safety Talk / The Investigation and Mitigation of Misfires - W. Reisz (International Society of Explosives Engineers, 2009)
Dealing with misfires can be one of the most difficult and serious issues that blasters must confront. Most of us will - at some point, have to deal with a misfire situation.